Identifikasi Pengaruh Perilaku Pengendara Sepeda Motor Terhadap Tingkat Kecelakaan Lalu Lintas Ditinjau Dari Faktor Manusia Menggunakan Metode Structural Equation Modelling - Suci Qurratul Aini (Ekonosfera: Jurnal Ekonomi, Akuntansi, Manajemen, Bisnis dan Teknik Global, 2025)
The increase in motorcycle ownership has not been anticipated by increased awareness of traffic safety. Awareness of driving safety is still lacking in the community, especially among motorcyclists. Factors causing traffic accidents are humans, vehicles, roads (infrastructure) and weather. Human factors have the highest causal factor for traffic accidents. The purpose of this study is to analyze the relationship between human factors on the safety of driving Syiah Kuala University students who ride motorcycles in Banda Aceh city. Data was obtained by distributing questionnaires through Google Forms to 300 motorcyclists. The research data were processed using Structural Equation Modeling (SEM) - Confirmatory Factor Analysis (CFA).